Superior mesenteric artery thrombosis in a child with chronic abdominal pain - A. Shamekh; L.L. Goldsworthy; S.A.K. Pullattayil; W. Mubarak; A. Shabani; C.V.E. Powell (Elsevier, 2021)
We present a case of a 13 year old boy with global developmental delay, due to leukoencephalopathy, recent onset of epilepsy and faltering growth. There was a background of chronic abdominal pain, considered to be gastroesophageal reflux disease. He presented with an acute exacerbation of his abdominal pain, abdominal distention and shock. Ultimately a superior mesenteric artery thrombosis was diagnosed and treated. This report focusses on the clinical features of this case along with the diagnostic approach. It illustrates this serious and rare but treatable cause of chronic abdominal pain which can be suspected by careful history taking.